BRAND BOYCOTT AND ISRAEL-HAMAS WAR 2023: MALAYSIA MCDONALDʼS AND STARBUCKS BRAND RESPONSE AND PERCEPTION - Ahmad Tajudin, Bazlin Darina; Eng , May Chuen; Jasmin, Nur Zahrawaani; Halil, Nur Afni; Wong, Michelle (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
With the escalation of the Israel-Hamas conflict on 7 October 2023, Palestinian supporters have called for boycotts of companies they claim support Israeli policies and have drawn millions of views on social media. Many of those boycotting have referred to the Boycott, Divestment, Sanctions (BDS) movement to target a few pro-Israel brands to make the boycott more effective, and two of the brands that have been most affected globally are Starbucks and McDonaldʼs. This research adopts a qualitative case study approach using content analysis of press statements, social media communications, and academic literature to explore brand responses and public perceptions in Malaysia. The study aims to (1) examine the response from McDonaldʼs and Starbucks to the boycott against them in Malaysia; and (2) investigate the intentions behind these responses during the boycott. Findings showed that the McDonald’s and Starbucks boycott cases in Malaysia serve as critical case studies of how global brands must navigate geopolitical sensitivities in culturally diverse markets.